Interactional Features of Teacher Talk and Their Influence on Student Participation in Indonesian EFL Classrooms - Nurkhaira Ariendita Fortuna, La Sunra, Vivit Rosmayanti (Journal of Educational Studies, 2025)
Classroom interaction in EFL settings is strongly shaped by how teachers manage talk and participation; however, limited research has examined how interactional features of teacher talk simultaneously support and constrain student participation in Indonesian secondary classrooms. This study investigates how teacher talk influenced student participation within public and Islamic junior high school contexts in Makassar, Indonesia. Employing a qualitative multiple case study design, the study involved three English teachers and nine students. Data were collected through classroom observations, video recordings, and semi-structured interviews. The analysis combined Self-Evaluation of Teacher Talk (SETT) framework analysis and thematic analysis to examine how teacher talk was enacted during classroom interaction. The findings revealed that display questions, teacher echo, extended teacher turns, and immediate evaluative feedback frequently maintained teacher-controlled interaction and produced short learner responses. In contrast, referential questions, extended wait time, and adaptive scaffolding created greater opportunities for elaborated responses and meaningful participation. However, excessive scaffolding and immediate correction often increased learner dependency on teacher guidance. The findings further indicated that participation was socially and culturally mediated through hierarchical teacher–student relationships and respect-oriented classroom communication. This study highlights the importance of balancing instructional support, learner autonomy, and interactional space to promote more dialogic participation in Indonesian EFL classrooms.